The Girl-child’s right to education in Nigeria: examining the adequacy of its protection by the state (2017)
Education gives children, especially the girl-child, hope for life and work. The right to education for girls enables them to reach their fullest potential. Education for all is a tool for change, a way out of poverty and a way to self-discovery and personal achievement. In the case of the girls’ education, not only does the problem lie in the question of discrimination as the foremost stronghold, but also of access to education due to certain limiting factors that affect girls' access to formal education. In order to access education, the girl-child must overcome a host of different barriers that stand between her and her goals. Lack of educational opportunities makes it difficult for the girl-child to enjoy other human rights, as the right to education is a basic right and a prerequisite to the enjoyment of all others. Two main issues are addressed in this paper; first, it addresses the barriers which hinder many girls in Nigeria from attending school, highlighting the benefits accrued to individuals and societies from educating girls. Second, the paper analyses the protection of this group of children and their plights in having access to free and compulsory primary education through the use of international human rights instruments and standards, their relation to national law and practice. This is aimed at improving the girls ’ access to education, serving as a call for Nigeria to provide education for all, especially girls who comprise the majority of out of school children in the country. Finally, it is revealed that Nigeria cannot stop the cycle of poverty, economic deprivation and poor health unless everyone has an equal opportunity to access education, most especially, its girls